The Association Between Sjögren Syndrome and Adverse Postoperative Outcomes: A Historical Cohort Study Using Administrative Health Data. Issue 4 (August 2016) - Babazade, Rovnat; Sun, Zhuo; Hesler, Brian D.; Sharma, Arjun; Makarova, Natalya; Dalton, Jarrod E.; Turan, Alparslan
Abstract : (Abstracted from Anesth Analg, 121:1222–1230, 2015) The chronic autoimmune disorder Sjögren syndrome has a known link to cardiovascular disease and events. The purpose of this study was to evaluate postoperative complications in patients with Sjögren syndrome undergoing noncardiac surgical procedures, to test the hypothesis that people with this disorder are at greater risk of developing cardiac complications than those without Sjögren syndrome.